(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Full coverage crowns remain a key restorative option for compromised or missing teeth, with marginal adaptation being critical for the longevity and success of the restoration. Therefore, the purpose of the present study is to compare the marginal fit of zirconia crowns with that of porcelain-fused-to-metal (PFM) crowns in endodontically treated teeth. Methods: This comparative in vitro study at the Department of Prosthodontics, Bangabandhu Sheikh Mujib Medical University (BSMMU), in collaboration with Beau-Dent, Dhaka, Bangladesh (January–December 2021), included 60 endodontically treated teeth equally divided into zirconia and PFM crown groups. Marginal gaps at mesial, distal, buccal, and lingual surfaces were measured with a stereomicroscope and compared using SPSS 25, with p < 0.05 considered significant. Results: Sixty endodontically treated teeth were equally assigned to zirconia (n = 30) and PFM (n = 30) groups. Participants had a mean age of 25.03 ± 2.76 years, with 56.7% females. Zirconia crowns showed significantly smaller mean marginal gaps (45.2 ± 5.8 µm) than PFM crowns (78.6 ± 9.4 µm, p < 0.001), with consistent gaps across all surfaces. Conclusion: Zirconia crowns provide superior and more consistent marginal fit than PFM crowns in endodontically treated teeth, supporting their clinical reliability. Journal of Paediatric Surgeons of Bangladesh (2024) Vol. 15 (1 & 2): 18-22